THE EFFECT OF GOOD CORPORATE GOVERNANCE ON TAX AVOIDANCE: EMPIRICAL STUDY OF THE INDONESIAN BANKING COMPANY - Waluyo Waluyo (The Accounting Journal of Binaniaga, 2017)
The purpose of this study aims to examine the effect of corporate governance on tax evasion. Corporate governance is proxied represented by the audit committee, the proportion of independent board of commissioners, institutional ownership and audit quality. Tax evasion is measured by the size of the gap of an effective tax rate. This study uses quantitative research design and data from the Finance Authority Service / OJK listed on the Indonesia Stock Exchange. By using purposive sampling in the observation period of 2013-2016, it has obtained 92 observations. The Data has been analyzed by using ordinary least square regression model. Regression results has identified that the proportion of independent board of commissioners and corporate performance have negatively affected tax evasion. Audit committees, audit quality and the size of company positively affected tax evasion. However, the institutional ownership has had no significant effect on tax evasion. These results have indicated that some of the mechanisms of corporate governance in Indonesia have been effective according to its function for the shareholders.Keywords: tax avoidance, corporate governance, audit committee, the proportion of independent board of commissioners, ownership institutional, audit quality.